PERFORMANCE ANALYSIS OF SMALL SCALE DESALINATION PLANT BASED ON MULTI TRAY AERATOR, MEDIA FILTER, AND SEAWATER REVERSE OSMOSIS - Danial, Mochammmad Meddy; Purnaini, Rizki; Khairi, Syahrul; Setiawan, Eric; Nadeak, Raymond; Septiansyah, Edo; Abshar, Khairul (Jurnal Teknik Sipil, 2022)
Seawater as abundant source for clean water is deemed as impossible task, particularly in developing country. Therefore, the feasibility of applying the reverse osmosis technology, particularly in the coastal area for drinking water is need further investigation. This paper aims to design and analyze the performance of small-scale desalination plant using combination of multi tray aerator, media filter, and multiple membranes consisting of ultrafiltration, brackish, and seawater membranes.Parameters used to verify the performance of small plant are salinity and total dissolved solid for membranes, while the parameters for examining the pre-treatment are Fe and Mn. The test results will be evaluated under the regulation of minister of health, Permenkes No. 32/2017. The influence of the pump pressure on the flow will also be analyzed.The result shows that the desalination plant can reduce the salinity concentration significantly from 10,200 ppm to 16 ppm, or 99.84%. The ratio of clean water to rejected water is 36%.  However, bacteria of E. Coli are still found in clean water, which is probably caused by biofouling.